On the stress intensity near the tips of interfacial boundary shear cracks at a corner point of the interface - Nazarenko, V. M.; Kipnis, A. L. (Reports of the National Academy of Sciences of Ukraine, 2015)
The symmetric problem of the theory of elasticity for interfacial shear cracks at a corner point of the media-separating boundary is considered. To solve the problem, the Wiener–Hopf method is used. The formula for the stress intensity factor is obtained.